Geology, chronology, fluid inclusions, and H–O–S isotopic compositions of the Hongyuntan magnetite deposit, Eastern Tianshan, NW China. (1st April 2019) - Sun, Zhi-Yuan; Long, Ling-Li; Wang, Yu-Wang; Luo, Zhao-Hua; Hu, Qi-Tao; Wang, Meng-Long
Graphical abstract: Highlights: The Hongyuntan magnetite deposit, NW China, formed at 324 ± 31 Ma. Four types of fluid inclusions can be identified during the metallogenic stages of the Hongyuntan deposit. The temperatures and salinities of the ore-forming fluids fluctuate from the early to the late stages. The ore-forming fluids were magmatic in origin and mixed with seawater during the late stage. Fluid mixing and fluid boiling were main potential mechanisms for the deposition of magnetite. Abstract: The Hongyuntan magnetite deposit, which is located in the Aqishan–Yamansu belt of Eastern Tianshan, Xinjiang, is hosted within Carboniferous submarine volcanic-sedimentary sequences. The deposit is characterized by five metallogenic stages: Stage I (garnet–diopside), Stage II (magnetite–tremolite–chlorite–pyrite), Stage III (magnetite–quartz–albite–actinolite), Stage IV (pyrite–quartz–epidote) and Stage V (hematite–limonite). Pyrite associated with magnetite formed during the Stage II has a Re-Os isochron age of 324 ± 31 Ma. Four types of fluid inclusions were observed in the mineral assemblages, namely, two-phase liquid and vapor inclusions, multi-phase daughter mineral-bearing inclusions, multi-phase CO2 -bearing inclusions, and monophase vapor inclusions. Microthermometry data reveal that the ore-forming fluids evolved from high-temperature (average 532.5 °C) and high-salinity (average 26.9 wt% NaCleqv) fluids to moderate–low-temperature (average 203.6 °C) and low-salinity (5.07 wt% NaCleqv) fluids. Magnetite precipitation may have been greatly assisted by mixing and boiling in Stage II and Stage III, respectively. The hydrogen and oxygen isotopic values of Stage I garnet (δDV-SMOW = −107.9‰ to −76.7‰, δ 18 Ofluid = 6.4–10.7‰) and Stage III quartz (δDV-SMOW = −85.5‰ to −83.2‰, δ 18 Ofluid = 3.8–4.7‰) indicate that the ore-forming fluids were dominated by magmatic water, whereas fluid mixing occurred during Stage II (δDV-SMOW = −117.3‰ to −112.6‰, δ 18 Ofluid = 3.3–5.7‰) and Stage IV (δDV-SMOW = −115.2‰ to −58.5‰, δ 18 Ofluid = −1.3‰ to 4.5‰). The variable δ 34 S values of pyrite (−3.8‰ to 4.7‰) and δ 18 Omgt values of magnetite (−0.6‰ to 4.1‰) suggest that they were not sourced from a single reservoir. The Hongyuntan magnetite deposit is spatially and temporally associated with volcanism and may be genetically related to it. The fluid inclusions and isotopic compositions of this deposit indicate that its ore-forming fluid was derived from the exsolution of deep-seated magmas and that fluid mixing could have effectively triggered the deposition of ore-forming materials. Multiple periods of volcanic activity could have incorporated additional heat and ore metals into the ore-forming system. Based on our data, we conclude that the origin of the Hongyuntan magnetite deposit is related to the volcanism in the Carboniferous period.